Pengaruh Desain Modular Terhadap Stabilitas Suhu dan Reduksi Kebisingan pada Incu Analyzer - prasojo, fajri; Andi Kurniawan Nugroho; Sri Heranurweni (Jurnal Transformatika, 2026)
Incu analyzer is a tool used to measure temperature, airflow noise and humidity. The way the tool works during calibration is placed on a mattress. The temperature sensor used is an LM35 sensor that produces a linear voltage value with temperature. The output voltage is proportional to the temperature in degrees Celsius. The noise level sensor uses a sound sensor microphone module, which is an electronic module that functions to detect sound and convert it into an electrical signal. This Sound Mic Microphone Sensor Detection Module for Arduino has a sound detection range of ± 30 cm to 1 meter. When testing the 35°C setting, the error percentage was 7%, the 36°C setting obtained a 3% error percentage and the 37°C setting obtained a 3% error percentage. The noise level sensor test data was carried out 9 times at 5 minute intervals. And the average error value was 1.2 (dB), and the overall error value was 0.92 (dB).